Here's to us ebook - Hilderbrand, Elin (2016)
Three romantic rivals in one crowded house equals plenty of room for jealousy in this surprising and heartwarming story from New York Times bestselling author Elin Hilderbrand. Laurel Thorpe, Belinda Rowe, and Scarlett Oliver share only two things; a love for the man they all married, Deacon Thorpe—a celebrity chef with an insatiable appetite for life—and a passionate dislike of one another. All three are remarkable, spirited women, but they couldn't be more different. Laurel: Deacon's high school sweetheart and an effortlessly beautiful social worker; Belinda: a high-maintenance Hollywood diva; and Scarlett: a sexy southern belle floating by on her family money and her fabulous looks. They've established a delicate understanding over the years—they avoid each other at all costs. But their fragile detente threatens to come crashing down after Deacon's tragic death on his favorite place on earth: a ramshackle Nantucket summer cottage. Deacon's final wish was for his makeshift family to assemble on his beloved Nantucket to say good-bye. Begrudgingly, Laurel, Belinda, and Scarlett gather on the island as once again, as in each of their marriages, they're left to pick up Deacon's mess. Now they're trapped in the crowded cottage where they all made their own memories—a house that they now share in more ways than one—along with the children they raised with Deacon, and his best friend. Laurel, Belinda, and Scarlett each had an unbreakable bond with Deacon—and they all have secrets to hide.  Before the weekend is over, there are enough accusations, lies, tears, and drama to turn even the best of friends—let alone three women who married the same man—into adversaries. As his unlikely family says good-bye to the man who brought them together—for better or worse—will they be able to put aside their differences long enough to raise a glass in Deacon's honor?